Transcriptome Analyses of In Vitro Exercise Models by Clenbuterol Supplementation or Electrical Pulse Stimulation - Taku Fukushima (MDPI AG, 2021)
Exercise has beneficial effects on human health and is affected by two different pathways; motoneuron and endocrine. For the advancement of exercise research, in vitro exercise models are essential. We established two in vitro exercise models using C2C12 myotubes; EPS (electrical pulse stimulation) for a motoneuron model and clenbuterol, a specific β2 adrenergic receptor agonist, treatment for an endocrine model. For clenbuterol treatment, we found that Ppargc1a was induced only in low glucose media (1 mg/mL) using a 1-h treatment of 30 ng/mL clenbuterol. Global transcriptional changes of clenbuterol treatment were analyzed by RNA-seq and gene ontology analyses and indicated that mitogenesis and the PI3K-Akt pathway were enhanced, which is consistent with the effects of exercise. Cxcl1 and Cxcl5 were identified as candidate myokines induced by adrenaline. As for the EPS model, we compared 1 Hz of 1-pulse EPS and 1 Hz of 10-pulse EPS for 24 h and determined Myh gene expressions. Ten-pulse EPS induced higher Myh2 and Myh7 expression. Global transcriptional changes of 10-pulse EPS were also analyzed using RNA-seq, and gene ontology analyses indicated that CaMK signaling and hypertrophy pathways were enhanced, which is also consistent with the effects of exercise. In this paper, we provided two transcriptome results of in vitro exercise models and these databases will contribute to advances in exercise research.